OVERPRODUCTION OF RECOMBINANT DNA POLYMERASE THERMUS THERMOPHILUS IN ESCHERICHIA COLI BL21-GOLD(DE3) AS WELL AS ITS PURIFICATION AND CHARACTERIZATION - Sulistiawati, Ayu
Polymerase Chain Reaction (PCR) method is widely used in molecular biotechnology for research and diagnostic purposes. DNA polymerase is an enzyme that plays an important role for in vitro DNA synthesis by PCR. One of the mostly used DNA polymerase is the Thermus thermophilus DNA polymerase (DNApol_Tth). The procurement of DNA polymerase in Indonesia is expensive and requires a long time as the consequences of importing DNA polymerase from other countries. The purpose of this study was to determine the optimal conditions for overproduction, purification, and characterization of recombinant DNApol_Tth in Escherichia coli BL21-GOLD(DE3). This recombinant DNApol_Tth is expected to be one of DNA polymerases that produced in Indonesia. Recombinant DNApol_Tth was overproduced by E. coli BL21-GOLD (DE3) as host cell in Luria-Bertani (LB) medium at 25°C, 20 hours, 150 rpm and induced with IPTG at final concentration 0.1 mM. This enzyme was purified using affinity chromatography of Ni-NTA resin and was eluted using 250 mM imidazole solution. The recombinant DNApol_Tth can synthesize PCR products with a size of up to 3,647 base pairs, resistant to PCR inhibitors i.e., blood up to 5% and 8% plasma, suitable to be used for detection in PCR and quantitative (qPCR) method, as well as has reverse transcriptase activity. Based on its profiles, recombinant DNApol_Tth produced in E. coli BL21-GOLD from this study is valuable to be up scaled to substitute imported DNA pol.